PENGARUH MODEL PEMBELAJARAN DISCOVERY DENGAN PENDEKATAN SAINTIFIK DAN KETERAMPILAN PROSES TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK - Nurul Hilmi; Ahmad Harjono; Harry Soeprianto (Jurnal Penelitian Pendidikan IPA, 2017)
This study aims to determine 1) Effect of discovery learning model with a scientific approach (PDPS) on learning outcomes physics learners; 2) The effect of process skills to the learning outcomes of physics students and 3) Effect of discovery learning model with a scientific approach interaction and process skills to the learning outcomes of students. This study is a quasi-experimental design using pretest-posttes nonequivalent group design with a 2 x 2 factorial design. Data were analyzed using analysis of variance with SPSS 21. The result showed 1) Model PDPS affect the Physics learning outcomes of learners with sig (0,000 ) <α (0.05), 2) process  skills  affects the outcome of the  learning physics learners with sig (0.001) <α (0.05) and 3) There is a learning model interaction effect (PDPs-Expository) and process skills to physics learning outcomes with sig (0,000) <α (0.05)Keywords: Discovery learning model with a scientific approach,  process skills, learning outcomes